Libraries and their users: collected papers in library history - Kaufman P. (London: The Library Association, 1969)
The papers here collected represent an effort in the main to construct a comprehensive view of those non-private collection in British community libraries. These collection of essays which appeared in in a variety of scholarly journals focus on three aspects: library catalogues; records of borrowings; and records of borrowers.
Includes index
uaa 23/01/19
Loans.
Keywords: Libraries; Library services; United Kingdom